Doppler evaluation of hepatic hemodynamics after living donor liver transplantation in infants - Chen, Xiping; Xiao, Huan; Yang, Chunjiang; Chen, Jingyu; Gao, Yang; Tang, Yi; Ji, Xiaojuan (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The aim of this study was to explore the hemodynamic changes of hepatic artery and portal vein detected by Doppler ultrasound (DU) in infants who underwent living donor liver transplantation (LDLT). Methods: The data of 41 infant patients (22 Males,19 Females, median age of five months) were collected in the Children's Hospital affiliated to the Chongqing Medical University from May 2018 to December 2019. The patients underwent left lateral segment LDLT (LLS -LDLT) because of biliary atresia (BA). Hemodynamic parameters, including the peak systolic velocity (PSV), resistivity index (RI) of the hepatic artery (HA), portal vein velocity (PVV), and portal vein flow (PVF) were recorded from Doppler ultrasound on the day before the operation，and on the 1st , the 7th , the 14th and the 30th day after LDLT procedures. The changes of PSVHA, RIHA, PVV and PVF before and on the 1st day after transplantation were analyzed by paired t-test. The comparison of the data between different postoperative time points were assessed by ANOVA. Results: Compared with the parameters measured before LDLT, PSVHA and RIHA decreased , and PVV and PVF increased significantly (P < 0.001) on the 1st day after LLS-LDLT. As for PSV, there was no significant difference between the 7t h day and the 1st day after transplantation (POD7 VS POD1, P =0.167) while there was a substantial difference between the 14th , 30th and 1st day after LT (POD14 VS POD1, P =0.003) (POD30 VS POD1, P ＜0.001). And there was a significant difference between the 14th , 30th and 7th days after LT (POD14 VS POD7, P =0.014) (POD30 VS POD7, P ＜0.001) . There was no significant difference between 30th and 14th after transplantation (POD30 VS POD14, P = 0.092). As for RIHA and PVV, the decrease was slow within the first month after the operation, and there was no significant difference at different times. Conclusion: We have identified major hepatic flow changes occurred in 41 infants underwent LLS-LDLT due to BA. The data could be used for future studies of LDLT in infants including hemodynamic modeling, liver regeneration and clinical management.